Goethe’s conception of “experiment as mediator” and implications for practical work in school science - Park, W; Song, J (Springer Verlag, 2018)
There has been growing criticism over the aims, methods, and contents of practical work in school science, particularly concerning their tendency to oversimplify the scientific practice with focus on the hypothesis-testing function of experiments. In this article, we offer a reading of Johann Wolfgang von Goethe’s scientific writings—particularly his works on color as an exquisite articulation of his ideas about experimentation—through the lens of practical school science. While avoiding the hasty conclusions made from isolated experiments and observations, Goethe sought in his experiments the interconnection among diverse natural phenomena and rejected the dualistic epistemology about the relation of humans and nature. Based on a close examination of his color theory and its underlying epistemology, we suggest three potential contributions that Goethe’s conception of scientific experimentation can make to practical work in school science.